The Józef Kostrzewski Poznań School of Archaeology. Several reflections on the illuminations and shadows of prehistory studies in respect to the Bronze and Early Iron Ages - Kaczmarek, Maciej; Minta-Tworzowska, Danuta (My University, 2012)
In the paper, the authors wish to reflect on Józef Kostrzewski’s research postulates in the context of passing time, in particular on the influence of his work on the further development of research on the Bronze and Early Iron Ages in the interfluvial region of the Odra and Vistula. Bearing in mind the vastness of issues, only two major research questions shall be addressed: cultural taxonomy (mainly in respect to the Lusatian culture) as well as and the chronology and periodisation of the abovementioned prehistory period in the general historical and methodological contexts.
Keywords: archaeology; Józef Kostrzewski; Poland; Poznań; Bronze Age; Early Iron Age